Pengaruh Kualitas Layanan, Citra Perusahaan Dan Kepercayaan Terhadap Kepuasan Pelanggan (Studi Kasus Pada Bank Bri Kcp Unit Lawang) - Muhammad Rizalfalal; M Hufron; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2020)
Abstract The purpose of this study was to determine the effect of Service Quality, Company Image and Trust on Customer Satisfaction. The population of this research is the customers of Bank BRI KCP Lawang Unit. Sampling using purposive sampling method and the number of samples used as many as 85 people. The model used in this study is multiple linear regression analysis. There is an Influence of Service Quality, Corporate Image and Trust on Customer Satisfaction at Bank BRI KCP Lawang Unit. Service quality has a significant effect on customer satisfaction at Bank BRI KCP Lawang Unit, Corporate Image has no effect on Customer Satisfaction at Bank BRI KCP Lawang Unit. Trust has a significant effect on customer satisfaction at Bank BRI KCP Lawang Unit.Keywords: Service Quality, Company Image, Trust, Customer Satisfaction